Islamic Ideal and Political Reality in Late-Classical Muslim Thought (American Journal of Islam and Society, 1986)
Like all great religions, Islam perceives God as the ruison &re of allthings? Moreover, as a comprehensive scheme, Islam seeks to mold everysphere of man’s life in accordance with the moral principles it propagates.The end of Islamic political thought thus is to materialize these principles.Because they are codified in a body of law, the Islamic polity may be referredto as a nomocracy, making Islamic political thought a legal enterprise.Moreover, unlike the Western tradition of political thought in which the discussionof the nature of the “state” plays a central role, the “state” as an artificialcorporate entity distinct from the community does not exist in Islamic politicalthought, but the “state” in the sense of a system of governance is a given.The primary question for any Islamic political thinker does not pertain tothe nature of the state, but rather to the leadership of the community, on theone hand, and the relationship of that community with other political communitieson the other. The political history of Islam has witnessed a host ofvarious ways by which the aforementioned concerns have been dealt with.Up to modem times and the emergence of a new breed of thinkers respondingto the Western impact, who deserve a category of their own, Islamicpolitical thought could be discerned from the works of the following fourgroups: the theologian jurisconsults (fuquha), the literalists or the authors ofthe mirrors of the princes (udaba), the historiadphilosophers (mu'arikhin),and the philosophers (falasifa) ...